Development of a polymerase chain reaction method for detection of a variant of vitamin K receptor, C1173T / Nurhidayati Mohamad - Mohamad, Nurhidayati (2007)
Background: Warfarin is an oral anticoagulant indicated for thromboembolism disorders. Warfarin antagonizes vitamin K epoxide reductase specifically the VKORCI subunit which is important in vitamin K recycle. However, the outcomes of warfarin. among individuals are highly variable and one of the factors causing inter-individual variabilities is due to genetic polymorphism of VKORC I l l 73C> T in intron 1. Patients with either heterozygous (l l 73CT) or homozygous (l l 73TT) mutation need lower average dose of warfarin to achieve therapeutic PT-INR. Aim: The purpose of this study is to develop a convenient and effective polymerase chain reaction (PCR) based method to detect variant ofVKORCl, Cl l 73T. Method: Optimization of direct-3-step polymerase chain reaction for detection of Cll 73T of VKORCI was performed. The PCR was conducted under different annealing temperatures using TaKaRa PCR Thermal Cycler Dice™ Gradient model to determine the optimal annealing temperature for this method. DNA sequencing was also performed on five samples to validate the PCR method. The optimiz.ed method is then used to genotype twenty DNA samples which were selected randomly from the DNA pool. Results: The PCR based method was successfully optimized according to the result of two positive controls. Genotyping of twenty randomly selected DNA samples showed all the samples were heterozygous for variant l l 73CT. Conclusion: Polymorphism at position 1173 in intron I of VKORCI significantly affects patient's response to warfarin and bleeding occurs even at normal dose. Hence, this optimized PCR method can be utilized to genotype patient for Cl l 73T variant prior to prescribing warfarin for personalized dose. Together with CYP2C9 genotyping, this approach can help to reduce the risk of bleeding without compromising the therapeutic effect of warfarin.